PENGARUH KEANDALAN INFORMASI AKUNTANSI, RELEVANSI INFORMASI AKUNTANSI DAN PERSEPSI MANAJEMEN ATAS KUALITAS AUDIT TERHADAP KINERJA KOPERASI - Yanti Insani, Novi; Indra Arza, Fefri; Rheza Syahrul, Alfatorry (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ The principal issues examined in this study is how to influence the reliability of accounting information , accounting information timeliness , and relevance of accounting information . This study aims to determine how much influence : 1 ) Reliability of accounting information on the performance of cooperative 2 ) Relevance of accounting information affects the performance of cooperative 3 ) Perception of management on the performance of the cooperative.This research was conducted in co-operatives registered with the Department of Cooperatives and SMEs Padang , the method in this research is a quantitative method . Where the population is 33 managers of cooperatives registered at the Department of Cooperatives and SMEs Padang. The data collected through questionnaires or questionnaire . Data analysis techniques of multiple linear regression.The results showed that : 1 ) a significant difference between the reliability of accounting information on the performance of the cooperative . This means that if the value of one variable increases the reliability of the unit will increase the value of the variable performance of a cooperative of 0,311 % . 2 ) a significant difference between the accuracy of the accounting relevance to the performance of the cooperative . This means that if the value of a variable timing increases 1 unit will increase the value of the variable performance of the cooperative at 0.195% . 3 ) a significant difference between the perceptions of management on the performance of the cooperative . If the value of the variable perception of an increase of 1 unit will increase the value relevance of 0.522% . So in conclusion the reliability of accounting information, accounting information timeliness , management perceptions significantly affect the performance of cooperatives in the city of Padang.